Improving Public Services: Exploring Hybrid Population Administration Service Innovations in Malang Regency - Afifuddin Afifuddin; Didik Supriyanto; Indra Kertati; Wahyu Wirasati; Satriadi Satriadi (Universitas Padjadjaran, 2023)
Population administration services are in charge as a crucial and strategic agent in ensuring the integrity of population data. In consequence, there is a requirement for the government to continuously improve and enhance the quality of these services. The research applies qualitative methods with a case study focus to examine the process and implications of a hybrid program that integrates government elements and spiritual values, known as Subuh Keliling Sukseskan Administrasi Kependudukan Terintegrasi (Suling Sakti). It was initiated by the Population and Civil Registration Office in Malang, East Java. In collecting data, this research applied observation, documentation, and interview techniques. The data analysis process is divided into three steps: data condensation, data presentation, and conclusion drawing or verification. The result found that the